(untitled) (Journal of the Bangladesh Agricultural University, 2017)
This study was conducted to assess the microbial load of Black Bengal goat meat during handling and selling in different markets of Mymensingh, Bangladesh. Total 27 samples were collected from three different places of the city, including KR market, Seshmore and Mesua Bazar. These samples were subjected to determine Total Viable Count (TVC), Total Coliform Count (TCC) and Yeast Mold Count (YMC) by using standard protocols. In raw meat, mean value of TVC were highest in Seshmore market (5.24±0.42 log cfu/g) at 0 hour but having no significant differences with other two places. In case of TCC and YMC highest count were in meat of Mesua Bazar. In case of TCC, difference were observed (P<0.05) among the markets. At 5 hours all the bacterial counts were increased having significant differences with the initial count and in most of the cases the bacterial count crossed the acceptable limit. This was may be due to the unhygienic practices of butchers. Consumers were not conscious. Suggestion has been given to improve the knowledge on hygiene among the meat producers to reduce microbial load.